Impact of etanercept tapering on work productivity in patients with early rheumatoid arthritis: results from the PRIZE study. Issue 2 (7th July 2016) - Zhang, Wei; Bansback, Nick; Sun, Huiying; Pedersen, Ronald; Kotak, Sameer; Anis, Aslam H
Abstract : Objective: To assess changes in work productivity in patients who have achieved response using etanercept (ETN) 50 mg+methotrexate (MTX) (phase I) are randomised to ETN 25 mg+MTX versus MTX versus placebo (phase II) and then withdrawn from treatment (phase III). Methods: Patients included in the analysis were in employment entering phase II of the PRIZE trial and had one or more follow-ups. Phase II was a 39-week, randomised and double-blind comparison of the 3 dose-reduction treatments. Phase III was a 26-week observational study where treatment was withdrawn. The Valuation of Lost Productivity was completed approximately every 13 weeks to estimate productivity impacts from a societal perspective. Results: A total of 120 participants were included in our analyses. During phase II, ETN25+MTX or MTX improved paid work productivity by over 100 hours compared with placebo, amounting to a gain of €1752 or €1503, respectively. ETN25+MTX compared with placebo gains €1862 in total paid/unpaid productivity. At week 52, the 3-month paid work productivity loss was 21.8, 12.8 and 14.0 hours, respectively. The productivity loss increased at week 64 from week 52, dropped at week 76 for all treatment groups and then continued rising after week 76 for the placebo group (71.9 hours at week 91) but not for the other 2 groups (21.9 hours for ETX25+MTX and 27.6 hours for MTX). Conclusions: The work productivity gain in phase I as a result of ETN50+MTX was marginally lost in the dose-reduction treatment groups, ETN25+MTX and MTX, but substantially lost in the placebo group during phase II. Trial registration number: NCT00913458; Results.